The “Matthew effect'” and market concentration: search complementarities and monopsony power - Fernández-Villaverde, J; Mandelman, F; Zanetti, F; Yu, Y (Centre for Economic Policy Research, 2021)
This paper develops a dynamic general equilibrium model with heterogeneous firms that face search complementarities in the formation of vendor contracts. Search complementarities amplify small differences in productivity among firms. Market concentration fosters monopsony power in the labor market, magnifying profits and further enhancing high-productivity firms' output share. Firms want to get bigger and hire more workers, in stark contrast with the classic monopsony model, where a firm aims to reduce the amount of labor it hires. The combination of search complementarities and monopsony power induces a strong ``Matthew effect'' that endogenously generates superstar firms out of uniform idiosyncratic productivity distributions. Reductions in search costs increase market concentration, lower the labor income share, and increase wage inequality